PEMBERDAYAAN MASYARAKAT DESA TEMUWUH, KECAMATAN DLINGO MELALUI KEGIATAN PELATIHAN PENGOLAHAN SUMBER BAHAN PANGAN LOKAL - Jatmika, Septian Emma Dwi; Maharani, Welny Putri; Oktavia, Fivetha Titik; Putri, Ofhie (Universitas Ahmad Dahlan, Yogyakarta, 2018)
The potential of Temuwuh Village in producing food is very good, so innovation on available food is needed. Generally, people process food such as cassava, ginger and tempeh in a simple way. Therefore, UK KKN students are moved to empower the community by providing training on making cakes made from mokaf flour, ginger powder and tempe nugget. The purpose of this training is to provide knowledge and business skills for the people of Temuwuh Village. The method of implementing the training includes the activities of nutrition counseling and product manufacturing practices. The impact of this activity is the increase of public knowledge about how to process the food and the development of a business prospect.